Oyster Mushroom (Pleurotus ostreatus) Ethanolic Extract Inhibits Pparg Expression While Maintaining the Methylation of the Pparg Promoter During 3T3-L1 Adipocyte Differentiation - Ariyanto EF; Farahana AK; Sudirman GSJ; Widiarsih E; Qomarilla N; Rahayu NS; Wikayani TP; Heryaman H; Wira DW; Triatin RD; Bashari MH; Pamela Y; et al. (Journal of Experimental Pharmacology)
Eko Fuji Ariyanto,1,2 Anastasya Kania Farahana,3 Gabriella Sachiko Jannesha Sudirman,3 Erlina Widiarsih,4 Nurul Qomarilla,5 Nurul Setia Rahayu,4 Tenny Putri Wikayani,5 Henhen Heryaman,1 Dwi Wahyudha Wira,1 Rima Destya Triatin,1,2 Muhammad Hasan Bashari,1 Yunisa Pamela,1 Yuni Susanti Pratiwi,1 Mohammad Ghozali1 1Department of Biomedical Sciences, Faculty of Medicine, Universitas Padjadjaran, Sumedang, West Java, Indonesia; 2Research Center for Medical Genetics, Faculty of Medicine, Universitas Padjadjaran, Bandung, West Java, Indonesia; 3Undergraduate Program of Medical Doctor, Faculty of Medicine, Universitas Padjadjaran, Sumedang, West Java, Indonesia; 4Molecular Genetics Laboratory, Faculty of Medicine, Universitas Padjadjaran, Bandung, West Java, Indonesia; 5Cell Culture Laboratory, Faculty of Medicine, Universitas Padjadjaran, Bandung, West Java, IndonesiaCorrespondence: Eko Fuji Ariyanto, Department of Biomedical Sciences, Faculty of Medicine, Universitas Padjadjaran, Sumedang, West Java, Indonesia, Tel +6281316099791, Email fuji@unpad.ac.idPurpose: This study aims to provide new insights into the potential of oyster mushroom (Pleurotus ostreatus) ethanolic extract in preventing obesity through the inhibition of Pparg expression and modulation of methylation level on Pparg promoter during 3T3-L1 adipocyte differentiation.Methods: This in vitro quantitative experimental study was conducted by treating the 3T3-L1 cell line differentiated using 0.5 mM methyl-isobutyl-xanthine, 1 μM dexamethasone, and 10 μg/mL insulin-containing medium with oyster mushroom ethanolic extract. The extract was obtained from 80 g of dried oyster mushroom powder extracted three times with 800 mL of ethanol, filtered, evaporated, and reconstituted in dimethyl sulfoxide (DMSO) to final concentrations of 0, 25, 50, and 100 μg/mL, with DMSO limited to 0.5% in all solutions. Pparg mRNA expression was quantified by qRT-PCR analysis and Pparg promoter methylation levels were measured quantitatively by pyrosequencing of bisulfite-treated DNA samples.Results: The addition of 25 μg/mL oyster mushroom ethanolic extract significantly suppressed Pparg mRNA expression with no significant change in the Pparg promoter methylation levels.Conclusion: Oyster mushroom ethanolic extract inhibited Pparg mRNA expression without altering Pparg promoter methylation, suggesting reduced adipocyte differentiation. This study emphasizes the potential of oyster mushroom in the prevention or treatment of obesity by inhibiting adipocyte differentiation. Keywords: obesity, oyster mushroom, Pparg expression, Pparg methylation, 3T3-L1